Scaling climate-smart agriculture: Towards co-creating business models in the input supply chains and finance chains - Wattel, Cor; Asseldonk, Marcel van; Gathiaka, John; Mulwa, Richard; Wesenbeeck, Lia van; Oostendorp, Remco; Recha, John W.M.; Radeny, Maren A.O.; Bosselaar, Jonne (2019)
This Info Note presents an exploration of CSA scaling options in the Nyando Basin area of Kisumu and Kericho Counties in Kenya, through partnerships in the value chain. It is part of the NWO-CCAFS research project “Climate-Smart Financial Diaries for Scaling in the Nyando Basin, Kenya”, led by the Amsterdam Centre for World Food Studies, in consortium with Wageningen Economic Research, University of Nairobi and the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in East Africa.